Caracterização estrutural in silico e produção heteróloga de uma manganês peroxidase de Ganoderma boninense - Silva, Thaise Rosa da (2025)
Ligninolytic enzymes are a group of biocatalysts capable of degrading lignin, one of the main components of the plant cell wall. Among them, manganese peroxidases (MnPs) stand out as heme proteins involved in the oxidation of aromatic compounds and the cleavage of the complex lignin structure, playing a key role in the conversion of lignocellulosic biomass. These enzymes are mainly produced by filamentous fungi, among which Ganoderma boninense is noteworthy, a basidiomycete pathogen widely recognized for its high enzymatic efficiency and extracellular secretion, but still little explored for biotechnological applications. The present study aimed to structurally characterize a MnP from G. boninense and to produce it heterologously in Escherichia coli, with a focus on its production, purification, characterization, and evaluation of its biotechnological potential. MnP sequences from Ganoderma spp. were retrieved from NCBI, and sequence QOW95911.1 was selected. After molecular weight, isoelectric point, and active site analyses, sequence alignment and phylogenetic tree construction were performed. The three-dimensional structure was modeled based on peroxidase A0A5C2RQX4.1 from Lentinus tigrinus, showing GMQE (0.93) and QMEAN (- 0.58) values, which indicate high structural reliability. The sequence, without the signal peptide and with codon optimization, was cloned into the pET32a(+) vector and expressed in E. coli Rosetta (DE3), under IPTG induction (1 mM, 37 °C, 4 h). Expression resulted in a recombinant protein of approximately 56 kDa, detected in the insoluble fraction by SDS-PAGE. After purification and refolding, an active form of the enzyme was recovered, although with low performance in enzymatic activity assays. In conclusion, the structural evaluation and recombinant production of the G. boninense MnP provide valuable insights for future optimizations in expression and activity, and reinforce the biotechnological potential of this enzyme in applications related to lignocellulosic biomass degradation and second-generation biofuel production.